PEMILIHAN MEDIA SOSIAL DI KALANGAN MAHASISWA UNTAG SURABAYA - Ratnasari, Dwi Diah Arum; Sudaryanto, Edy; Rochim, Achludhin Ibnu (Universitas 17 Agustus 1945 Surabaya, 2015)
This research is motivated by social media election conducted by current students. Globalization isgrowing rapidly and sophisticated technology becomes a factor flourishing of social media. Account orownership of social media has become commonplace owned for communication activities. Social media isa medium for interaction that can facilitate in establishing communication between students who are insix faculties. Motivation is used in the selection of social media namely Motivation Diversion(Entertainment), Motivation Personal Identity (Fostering Social Affairs), and Motivation Cognitive(Knowledge). The method used in this study is a survey method is a method of research usingquestionnaires with Guttman scale as a data collection instrument. While this kind of research isdescriptive quantitative research. This study uses a model that considers the Uses and Gratificationactive audiences use media to meet their needs. It encourages the writer to determine whether themotivation - the motivation to make the reason the students in choosing social media uses.Keywords: selection, social media, motivation, students